IMPLEMENTASI PEMBELAJARAN SEJARAH SECARA DARING DENGAN MENGGUNAKAN E-LEARNING MADRASAH PADA KELAS X IPS 1 MAN 2 PONTIANAK - Putri Andriani; Nuraini Asriati; Edwin Mirzachaerulsyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine the implementation of online history learning usingMadrasah E-learning in class X IPS 1 MAN 2 Pontianak. This research usesdescriptive qualitative research method. Informants in this study included historyteachers, students of class X IPS 1, and waka of the curriculum. Data collectiontechniques using observation, interviews and documentation. Data analysistechniques include data collection, data reduction, data presentation, anddrawing conclusions. The results of this study indicate: First, the planning ofhistory learning carried out by the teacher is making learning tools in the formof syllabus, lesson plans, teaching materials, and preparing supporting devicessuch as laptops, cellphones and internet connections. Second, the implementationof history learning consists of preliminary, core and closing activities. Theimplementation of the learning process using Madrasah E-learning has not runoptimally because it is not in accordance with the learning implementation plan(RPP) that has been made by the previous teacher. Third, the evaluation ofhistory learning on the assessment of knowledge and skills is carried out by givingassignments through a Computer Based Test on E-learning Madrasas, while theassessment of the attitude aspect is seen from attendance through E-learningMadrasah.Keywords : Online Learning, History Learning, E-learning Madrasah